Screening, identification and evaluation of an acidophilic strain of Bacillus velezensis B4-7 for the biocontrol of tobacco bacterial wilt - Meng, Xiang-jia; Wang, Lan-qin; Ma, Bai-ge; Wei, Xi-hong; Zhou, Yi; Sun, Zheng-xiang; Li, Yan-yan (Frontiers in Plant Science, 2024)
Tobacco (Nicotiana tabacum L.) bacterial wilt, caused by Ralstonia solanacearum, is indeed a highly destructive plant disease, leading to substantial damage in tobacco production. While biological control is considered an effective measure for managing bacterial wilt, related research in this area has been relatively limited compared to other control methods. In order to discover new potential antagonistic bacteria with high biocontrol efficacy against tobacco bacterial wilt, we conducted an analysis of the microbial composition differences between disease-suppressive and disease-conducive soils using Illumina sequencing. As a result, we successfully isolated six strains from the disease-suppressive soil that exhibited antibacterial activity against Ralstonia solanacearum. Among these strains, B4-7 showed the strongest antibacterial activity, even at acidic conditions with a pH of 4.0. Based on genome analysis using Average Nucleotide Identity (ANI), B4-7 was identified as Bacillus velezensis. In greenhouse and field trials, strain B4-7 significantly reduced the disease index of tobacco bacterial wilt, with control efficiencies reaching 74.03% and 46.88% respectively. Additionally, B4-7 exhibited plant-promoting abilities that led to a 35.27% increase in tobacco production in field conditions. Quantitative real-time (qPCR) analysis demonstrated that strain B4-7 effectively reduced the abundance of R. solanacearum in the rhizosphere. Genome sequencing and Liquid Chromatography-Mass Spectrometry (LC-MS) analysis revealed that strain B4-7 potentially produces various lipopeptide metabolites, such as microlactin, bacillaene, difficidin, bacilysin, and surfactin. Furthermore, B4-7 influenced the structure of the rhizosphere soil microbial community, increasing bacterial abundance and fungal diversity, while also promoting the growth of different beneficial microorganisms. In addition, B4-7 enhanced tobacco’s resistance to R. solanacearum by increasing the activities of defense enzymes, including superoxide dismutase (SOD), phenylalanine ammonia-lyase (PAL), peroxidase (POD), catalase (CAT), and polyphenol oxidase (PPO). Collectively, these findings suggest that B. velezensis B4-7 holds significant biocontrol potential and can be considered a promising candidate strain for eco-friendly management of tobacco bacterial wilt.